Magnetic lubricating oil and preparation method thereof

The high cost and instability of existing magnetofluids in the lubricant field are solved by using low viscosity polya-olefins, metallocene polya-olefins and polyester compounds in lubricant in combination with homemade graphene polar composites. The excellent performance and stability of magnetic lubricating oil are achieved.

CN119490882APending Publication Date: 2025-02-21GUANGDONG SANVO HLDG CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311039095.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-16
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The application of existing magnetic fluids in the field of lubricating oils is limited by high cost and liquid stability issues, and the nanometal powders are not dispersed well in oil and are unstable.

Method used

Low viscosity polya-olefin, metallocene polya-olefin and polyester compounds are used as base oils, and graphene magnetic nanopowders are uniformly dispersed in the oily liquid by homemade graphene polar composite agent to form a stable polar network Oil film.

Benefits of technology

The excellent viscosity-temperature performance, shear stability, thermal oxidation stability, hydrolysis stability and low-temperature flow of magnetic lubricating oil are achieved, providing good anti-wear and lubrication effects, and maintaining magnetic stability at high temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FDA0004400145930000011
    Figure FDA0004400145930000011
Patent Text Reader

Abstract

The invention discloses magnetic lubricating oil and a preparation method thereof. The magnetic lubricating oil mainly comprises 70-85 parts of low-viscosity poly-alpha-olefin base oil, 8-14 parts of metallocene poly-alpha-olefin base oil, 5-10 parts of a polyester compound, 4-11 parts of a self-made graphene polar complexing agent and 0.3-0.8 part of a pour point depressant. The lubricating oil has the advantages that 1, the low-viscosity poly-alpha-olefin, the metallocene poly-alpha-olefin and the polyester compound are adopted, so that a stable polar network oil film can be formed, and good anti-wear and lubricating effects are provided; 2, the self-made graphene polar complexing agent has excellent dispersity and compatibility in base oil, graphene is uniformly dispersed on the polar net oil film, the heat-conducting property of the polar net oil film can be enhanced, heat dissipation of equipment is effectively facilitated, the polar net oil film is adsorbed on the surface of a metal friction pair like a magnet, equivalently, the polar net oil film is endowed with magnetism, and the magnetic property of the polar net oil film is improved; the adhesive force and stability of the net oil film are improved, the friction coefficient is reduced, and the service life of equipment is remarkably prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of magnetic lubricating oil, in particular to a magnetic lubricating oil and a preparation method thereof. Background Art

[0002] Nowadays, the rapid development of nanotechnology has led to its widespread use in biomedical applications and diagnostics. Among inorganic nanoparticles, magnetic nanoparticles have attracted great attention because the biocompatibility of these magnetic particles has been confirmed.

[0003] Magnetic lubricant is a kind of magnetic fluid. At present, due to the high cost and liquid stability problems that have not been completely solved, it is rarely used in automotive lubricants and industrial lubricants. However, due to its excellent anti-wear and friction reduction performance, it is only a matter of time before it is popularized in automotive lubricants and industrial lubricants. The sensitivity of lubricant viscosity to temperature is determined by the viscosity index. The viscosity index is an important indicator for determining the quality of lubricants and an important indicator for measuring the influence of temperature changes on lubricants. It is also called the viscosity-temperature performance of lubricants. The larger the viscosity index of lubricants, the less the viscosity of lubricants is affected by temperature. The smaller the viscosity index, the more sensitive the viscosity is to temperature. Lubricants with poor viscosity-temperature performance will also cause oil film instability due to unstable viscosity, which will increase dry wear of equipment. The detergency and dispersion performance, extreme pressure and anti-wear performance, thermal oxidation stability and low-temperature fluidity of lubricants are also very important. Nanographene is a popular new material in recent years. Lubricants prepared with graphene are magnetic, which gives lubricants high magnetic permeability, which is particularly obvious in weak and medium magnetic fields. Compared with traditional lubricants, magnetic lubricants have better anti-wear and friction reduction properties and better thermal conductivity.

[0004] There are many public technical studies on magnetic fluid. CN110534329A discloses a method for preparing an iron-nickel alloy magnetic fluid, which comprises heat-treating the iron-nickel alloy to magnetize the iron-nickel alloy; polishing the heat-treated iron-nickel alloy to obtain an iron-nickel alloy polishing liquid; washing the iron-nickel alloy polishing liquid with ultrasonic oscillation; centrifugally washing the iron-nickel alloy polishing liquid after ultrasonic oscillation washing with ethanol to obtain iron-nickel alloy nanosheets; activating the iron-nickel alloy nanosheets with acetone; surface-modifying the activated iron-nickel alloy nanosheets and centrifugally separating them; dispersing the surface-modified iron-nickel alloy nanosheets in a liquid medium to obtain an iron-nickel alloy magnetic fluid. The preparation method can prepare an iron-nickel alloy magnetic fluid without using expensive iron-nickel alloy nanoparticles, which reduces the preparation cost of the iron-nickel alloy magnetic fluid and promotes the popularization and application of the iron-nickel alloy fluid. CN109686526A discloses a magnetic fluid stable under strong magnetic field conditions and a preparation method thereof. A urea solution is added dropwise to an acetylacetonate iron solution, and then stirred to react to obtain a reaction solution 1; a stabilizer solution is added to the reaction solution 1 under stirring conditions, and then stirred to react to obtain a reaction solution 2; the reaction solution 2 is heated, centrifuged and washed to obtain a magnetic powder coated with a titanate coupling agent; the magnetic powder, carrier liquid and dispersant are mixed and ultrasonically dispersed to obtain a stable magnetic fluid. The magnetic saturation intensity of the prepared magnetic fluid is 100-500GS; the stability coefficient of the magnetic fluid under a 300KJ / m3 magnet does not change within six months, and the magnetic fluid has good stability under a strong magnetic field. CN103531324A discloses a preparation method for FeO magnetic fluid, which solves the problems of the existing method for preparing Fe3O4 magnetic fluid, that the morphology and particle size of Fe3O4 are difficult to control, the yield is low and the cost is high. Steps: 1. Prepare iron oleate; 2. Stir; 3. Heat. The advantages of the present invention are as follows: 1. The morphology and particle size of Fe3O4 in the Fe3O4 magnetic fluid prepared by the present invention are controllable; 2. The equipment required for the Fe3O4 magnetic fluid prepared by the present invention is simple and the production cost is low; 3. The yield of the Fe3O4 magnetic fluid prepared by the present invention is greater than 90%, and it is easy to industrialize production. The Fe3O4 magnetic fluid prepared by the present invention can be applied to vacuum dynamic seals, speakers, dampers, shock absorbers and mineral processing fields.

[0005] Currently, the related patents of magnetic fluid rarely involve the field of lubricating oil, and most of them use nanopowders containing metal elements as raw materials. The dispersion effect in oily liquids is poor, and the prepared suspension is extremely unstable. Nanometal powders are easy to agglomerate and settle in oil, and are easily demagnetized and lose their magnetism at high temperatures. Summary of the invention

[0006] The purpose of the present invention is to overcome the technical defects mentioned above and provide a magnetic lubricant having excellent viscosity-temperature performance, shear stability, thermal oxidation stability, hydrolysis stability and low-temperature fluidity, which can form a stable polar network oil film with strong adsorption force, provide good anti-wear and lubrication effects, and graphene has excellent dispersibility and compatibility in oily liquids, and is not easily demagnetized at high temperatures, and a preparation method thereof.

[0007] A magnetic lubricating oil of the present invention is realized in this way, and its formula is as follows in parts by weight: Low viscosity poly-a-olefin 70-85 parts Metallocene poly α-olefin 8-14 parts 5-10 parts of polyester compound 4 to 11 parts of homemade graphene polar composite Pour point depressant 0.3-0.8 parts.

[0008] The low-viscosity poly-a-olefin has a kinematic viscosity of 4 to 8 centistokes at 100°C and a viscosity index of more than 135; the metallocene poly-a-olefin has a kinematic viscosity of 600 to 700 centistokes at 100°C and a viscosity index of more than 270; the polyester compound is a mixture of trimethylolpropane ester and polyol ester, the kinematic viscosity of the polyester compound is between 4 and 6 centistokes at 100°C and a viscosity index of more than 127, and in the polyester compound, the weight ratio of trimethylolpropane ester to polyol ester is 2-4:6-8.

[0009] The self-made graphene polar composite agent is achieved as follows: According to weight ratio, add 50% extreme pressure anti-wear agent, 8% antioxidant, 20% dispersant, 6% rust inhibitor, 3% surfactant, 3% graphene magnetic nanopowder, and 10% low-viscosity hydrogenated base oil into the reactor, stir and heat to 50-70°C, maintain the temperature at 50-70°C and continue stirring and mixing for 2-6 hours, then maintain the temperature at 50-70°C for ultrasonic dispersion for 8-12 hours to obtain the self-made graphene polar composite agent.

[0010] Preferably, the extreme pressure anti-wear agent comprises triphenyl thiophosphate, thiophosphate ester, ammonium thiophosphate salt, sulfided olefin, and thioamino ester. Preferably, in the extreme pressure anti-wear agent, the weight ratio of triphenyl thiophosphate, thiophosphate ester, ammonium thiophosphate salt, sulfided olefin, and thioamino ester is 1-3:5-8:1-2:1-2:1-1.5.

[0011] Preferably, the antioxidant comprises alkyl diphenylamine, alkyl phenyl propionate and 2,6-di-tert-butyl-p-cresol. Preferably, in the antioxidant, the weight ratio of alkyl diphenylamine, alkyl phenyl propionate and 2,6-di-tert-butyl-p-cresol is 4-7:2-4:1-2.

[0012] Preferably, the rust inhibitor comprises butylene diacid, oleic acid glycol ester, pentaerythritol monooleate and 1,2,3-trimethylbenzotriazole. Preferably, in the rust inhibitor, the weight ratio of butylene diacid, oleic acid glycol ester, pentaerythritol monooleate and 1,2,3-trimethylbenzotriazole is 2-6:3-5:1-3:1-2.

[0013] Preferably, the surfactant comprises sodium dodecylbenzene sulfonate, oleic acid and maleic anhydride. Preferably, in the surfactant, the weight ratio of sodium dodecylbenzene sulfonate, oleic acid and maleic anhydride is 4-6:2-5:1-2.

[0014] Preferably, the dispersant comprises boronated polyisobutylene polysuccinimide, monosuccinimide ashless dispersant and benzylamine. Preferably, in the dispersant, the weight ratio of boronated polyisobutylene polysuccinimide, monosuccinimide ashless dispersant and benzylamine is 2-6:3-5:1-3.

[0015] Preferably, the pour point depressant comprises polymethacrylate pour point depressant, alkyl naphthalene, and poly α-olefin pour point depressant. Preferably, in the pour point depressant, the weight ratio of polymethacrylate pour point depressant, alkyl naphthalene, and poly α-olefin is 6-8:1-2:1-2.

[0016] The preparation method of the magnetic lubricating oil comprises the following steps: According to the weight ratio of the formula, low-viscosity poly-a-olefin, metallocene poly-a-olefin base oil and polyester compound are put into a reaction kettle, stirred and heated, and then the homemade graphene polar composite agent and pour point depressant are added, and stirred evenly at a constant temperature to obtain the finished product.

[0017] The magnetic lubricating oil of the present invention has the following beneficial effects: 1. Low-viscosity poly-a-olefin base oil, metallocene poly-a-olefin base oil and polyester compounds are used, which have excellent viscosity-temperature performance, shear stability, thermal oxidation stability, hydrolysis stability and low-temperature fluidity, and can form a stable polar network oil film with strong adsorption force, providing good anti-wear and lubrication effects; 2. The self-made graphene polar composite has excellent dispersibility and compatibility in the base oil. Graphene is evenly dispersed on the polar mesh oil film, which can enhance the thermal conductivity of the polar mesh oil film and effectively help the equipment dissipate heat. The polar mesh oil film is adsorbed on the surface of the metal friction pair like a magnet, which is equivalent to giving the polar mesh oil film magnetism, thereby improving the adhesion and stability of the mesh oil film, reducing the friction coefficient, and significantly extending the service life of the equipment. DETAILED DESCRIPTION

[0018] The following examples illustrate the present invention, but the present invention is not limited by these examples. Modifications to the specific embodiments of the present invention or equivalent replacement of some technical features without departing from the spirit of the present invention should be included in the scope of the technical solution claimed by the present invention.

[0019] The homemade graphene polar composite is achieved as follows: According to weight ratio, add 50% extreme pressure anti-wear agent, 8% antioxidant, 20% dispersant, 6% rust inhibitor, 3% surfactant, 3% graphene magnetic nanopowder, and 10% low-viscosity hydrogenated base oil into the reactor, stir and heat to 60°C, maintain the temperature at 60°C and stir and mix for 5.5 hours, then maintain the temperature at 60°C for 10 hours for ultrasonic dispersion, and you can get the self-made graphene polar composite.

[0020] Example 1 This embodiment provides a method for preparing magnetic lubricating oil: According to the weight ratio of the formula, 81.2 parts of low-viscosity polya-olefin, 8 parts of metallocene polya-olefin base oil and 5 parts of polyester compound are put into the reaction kettle, stirred and heated, and then 5 parts of homemade graphene polar composite agent and 0.8 parts of pour point depressant are added, and stirring is continued for 4 hours at 60°C until the mixture is evenly mixed to obtain the finished product.

[0021] Example 2 This embodiment provides a method for preparing magnetic lubricating oil: According to the weight ratio of the formula, 72.5 parts of low-viscosity polya-olefin, 10 parts of metallocene polya-olefin base oil and 9 parts of polyester compound are put into the reaction kettle, stirred and heated, and then 8 parts of homemade graphene polar composite agent and 0.5 parts of pour point depressant are added, and stirring is continued for 4 hours at 60°C until the mixture is evenly mixed to obtain the finished product.

[0022] Example 3 This embodiment provides a method for preparing magnetic lubricating oil: According to the weight ratio of the formula, 70.7 parts of low-viscosity polya-olefin, 13 parts of metallocene polya-olefin base oil and 6 parts of polyester compound were put into the reactor, stirred and heated, and then 10 parts of homemade graphene polar composite agent and 0.3 parts of pour point depressant were added, and stirring was continued for 4 hours at 60°C until the mixture was evenly mixed to obtain the finished product.

[0023] Comparative Example 4 This embodiment provides a method for preparing magnetic lubricating oil: According to the weight ratio of the formula, 57.8 parts of 150N base oil and 25 parts of 500N base oil were put into the reactor, stirred and heated to 60°C, and then 9 parts of the homemade graphene polar composite agent, 8 parts of OCP viscosity index improver and 0.2 parts of polymethacrylate pour point depressant were added, and the temperature was maintained at 60°C and stirring was continued for 4 hours until the mixture was uniform, thereby obtaining the finished product.

[0024] The relevant performance test results of a magnetic lubricating oil obtained in Examples 1 to 3 and Comparative Example 4 are shown in Table 1 below.

[0025] Table 1 It can be seen from the above table that compared with the prior art (Comparative Example 4), the magnetic lubricating oil of the present invention has a stable oil sample and no sediment, and the homemade graphene polar composite agent will not agglomerate and settle even if stored for a long time; it has a high viscosity index and excellent viscosity-temperature performance, and has excellent viscosity retention ability at high and low temperatures; it has a low pour point and excellent low-temperature flowability; the wear spot diameter and the average friction coefficient are low, which significantly improves the tribological properties of the magnetic lubricating oil and improves the extreme pressure and anti-wear properties of the magnetic lubricating oil; it has good magnetic retention ability at high temperatures and is not easily demagnetized, thereby ensuring the magnetic stability of the polar mesh oil film, improving the adhesion and toughness strength of the polar mesh oil film, and providing excellent lubrication performance for the equipment.

[0026] Main material information 1. Low viscosity poly-a-olefin base oil, industrial grade, supplied by Shanghai Nak Lubrication Technology Co., Ltd.; 2. Metallocene poly-a-olefin base oil, industrial grade, supplied by Shanghai Nak Lubrication Technology Co., Ltd.; 3.OCP viscosity index improver, industrial grade, commercially available; 4Trimethylolpropane ester and polyol ester, the supplier is Hangzhou Youmi Chemical Co., Ltd.; 5. Low viscosity hydrogenated base oil, base oil 150N, 500N, industrial grade, supplier is Formosa Petrochemical Corporation; 6. Triphenyl thiophosphate, thiophosphate esters, ammonium thiophosphate salts, sulfided olefins, thioamino esters, technical grade, commercially available; 7. Hindered phenol, alkyl diphenylamine, alkyl phenyl propionate, 2,6-di-tert-butyl-p-cresol, technical grade, commercially available; 8. Ethylene dicarboxylic acid, oleic acid glycol ester, pentaerythritol monooleate, 1,2,3-trimethylbenzotriazole, technical grade, commercially available; 9. Sodium dodecylbenzene sulfonate, oleic acid, maleic anhydride, technical grade, commercially available; 10. Borated polyisobutylene polysuccinimide, monosuccinimide ashless dispersant, benzylamine, technical grade, commercially available; 11. Polymethacrylate pour point depressant, alkyl naphthalene, poly α-olefin pour point depressant, technical grade, commercially available; 12. Graphene magnetic nanopowder, industrial grade, commercially available.

Claims

1. A magnetic lubricating oil, characterized in that: The proportion of each component by weight is:

2. A magnetic lubricant as claimed in claim 1, characterized in that: The low-viscosity poly-a-olefin has a kinematic viscosity of 4 to 8 centistokes at 100°C and a viscosity index of more than 135; the metallocene poly-a-olefin has a kinematic viscosity of 600 to 700 centistokes at 100°C and a viscosity index of more than 270; the polyester compound is a mixture of trimethylolpropane ester and polyol ester, the kinematic viscosity of the polyester compound is between 4 and 6 centistokes at 100°C and a viscosity index of more than 127, and in the polyester compound, the weight ratio of trimethylolpropane ester to polyol ester is 2-4:6-8.

3. A magnetic lubricant as claimed in claim 1, characterized in that: The self-made graphene polar composite agent is achieved as follows: According to weight ratio, add 50% extreme pressure anti-wear agent, 8% antioxidant, 20% dispersant, 6% rust inhibitor, 3% surfactant, 3% graphene magnetic nanopowder, and 10% low-viscosity hydrogenated base oil into the reactor, stir and heat to 50-70°C, keep the temperature at 50-70°C and continue stirring and mixing for 2-6 hours, then keep the temperature at 50-70°C for ultrasonic dispersion for 8-12 hours to obtain the self-made graphene polar composite.

4. The self-made graphene polar composite agent as claimed in claim 3, characterized in that, The extreme pressure anti-wear agent includes triphenyl thiophosphate, thiophosphate ester, ammonium thiophosphate salt, sulfided olefin, and thioamino ester. In the extreme pressure anti-wear agent, the weight ratio of triphenyl thiophosphate, thiophosphate ester, ammonium thiophosphate salt, sulfided olefin, and thioamino ester is 1-3:5-8:1-2:1-2:1-1.

5.

5. The self-made graphene polar composite agent as claimed in claim 3, characterized in that, The antioxidant comprises alkyl diphenylamine, alkyl phenyl propionate and 2,6-di-tert-butyl-p-cresol. In the antioxidant, the weight ratio of alkyl diphenylamine, alkyl phenyl propionate and 2,6-di-tert-butyl-p-cresol is 4-7:2-4:1-2.

6. The self-made graphene polar composite agent as claimed in claim 3, characterized in that, The rust inhibitor comprises butylene diacid, oleic acid glycol ester, pentaerythritol monooleate and 1,2,3-trimethylbenzotriazole. In the rust inhibitor, the weight ratio of butylene diacid, oleic acid glycol ester, pentaerythritol monooleate and 1,2,3-trimethylbenzotriazole is 2-6:3-5:1-3:1-2.

7. The self-made graphene polar composite agent as claimed in claim 3, characterized in that, The surfactant comprises sodium dodecylbenzene sulfonate, oleic acid and maleic anhydride. In the surfactant, the weight ratio of sodium dodecylbenzene sulfonate, oleic acid and maleic anhydride is 4-6:2-5:1-2.

8. The self-made graphene polar composite agent as claimed in claim 3, characterized in that, The dispersant comprises boronated polyisobutylene polysuccinimide, monosuccinimide ashless dispersant and benzylamine. In the dispersant, the weight ratio of boronated polyisobutylene polysuccinimide, monosuccinimide ashless dispersant and benzylamine is 2-6:3-5:1-3.

9. A magnetic lubricant as claimed in claim 1, characterized in that: The pour point depressant comprises polymethacrylate pour point depressant, alkyl naphthalene and poly α-olefin pour point depressant. In the pour point depressant, the weight ratio of polymethacrylate pour point depressant, alkyl naphthalene and poly α-olefin is 6-8:1-2:1-2.

10. The magnetic lubricant according to claim 1, characterized in that: The preparation method comprises the following steps: According to the weight ratio of the formula, low-viscosity poly-a-olefin, metallocene poly-a-olefin base oil and polyester compound are put into a reaction kettle, stirred and heated, and then the homemade graphene polar composite agent and pour point depressant are added, and stirred evenly at a constant temperature to obtain the finished product.

Citation Information

Patent Citations

  • Method for preparing Fe3O4 magnetic fluid

    CN103531324A

  • Stable magnetic fluid under strong magnetic field condition and preparation method of stable magnetic fluid

    CN109686526A

  • Preparation method for iron-nickel alloy magnetic fluid

    CN110534329A